THE EFFECT OF WASTE MANAGEMENT POLICY IMPLEMENTATION ON THE EFFECTIVENESS OF WASTE REDUCTION THROUGH 3R TPS IN SUKABUMI CITY - Nesya Nur Halimah; Tuah Nur; Rizki Hegia Sampurna (DIA: Jurnal Administrasi Publik, 2025)
This study aims to determine the effect of waste management policy implementation on the effectiveness of waste management in Sukabumi City. This research method uses quantitative with associative approach. The population of this study was the people of Sukabumi City. The sampling technique in this study used probability sampling technique with cluster random sampling so that each sub-district in Sukabumi City could be represented with a total sample of 100 people. Data were collected using observation, documentation, questionnaires and interviews. Simple linear regression analysis test was conducted for data analysis in this study. The findings of this study are based on the results of hypothesis testing, the variable of waste management policy implementation affects the effectiveness of waste reduction variable by 0.468 or 46.78%. Based on the results of the study, it is known that the correlation coefficient test obtained a positive correlation value of 0.684 which shows the closeness of the strong category. This means that the effect of management policy implementation on the effectiveness of waste reduction is 46.78%, while 53.22% is influenced by other factors not examined in this study.